Data Transmission Framework for the Internet of Things: Safe and Power-Proficient - Pradeepa, K.; Parveen, M. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Researchers and corporations have been paying close attention to the Internet of Things (IoT) concept lately. Building different smart systems, such the smart grid, smart city, and smart healthcare, requires a base station in the Internet of Things to handle data that is collected from millions of sensor devices. To guarantee the accuracy of the data collected, a secure link needs to be established between the base station and the sensor units. If the information is tainted, the results of the data analysis will be inaccurate and result in more serious harm. In addition, many IoT gadgets have relatively little interaction because of their incredibly low-power computational CPUs. A critical performance measure to take into account while developing a routing algorithm with low-power IoT devices is power efficiency. Thus, a secure and energy-efficient data transmission framework (SE-DTF) for the Internet of Things was introduced in this research. The results of the experiment show how safely a public and a secret key may be shared with a token via the IoT-PSKTS algorithm. It also proves that the throughput, power consumption, and packet delivery ratio of the MPCR using the HFLC algorithm are better than those of other methods. It also shows that compared to other cryptography systems, the two-tier cryptography methodology consumes less energy and requires less processing time for encryption and decoding.